1996
DOI: 10.1172/jci118549
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of acute inflammatory responses to biomaterials.

Abstract: The frequent inflammatory responses to implanted medical devices are puzzling in view of the inert and nontoxic nature of most biomaterials. Because implant surfaces spontaneously adsorb host proteins, this proteinaceous film is probably important in the subsequent attraction of phagocytes. In fact, earlier we found that acute inflammatory responses to experimental polyethylene terephthalate implants in mice require the precedent adsorption of one particular host protein, fibrinogen. The present investigations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
155
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(158 citation statements)
references
References 50 publications
3
155
0
Order By: Relevance
“…accessibility of the Fc parts of the molecules on the surface to the corresponding neutrophil receptors FcgRs), or simply the ligand density on the surface, which is determined by the physicochemical property of the supporting surface. Our results on the effect of surface-adsorbed albumin are in agreement with earlier observations [13][14][15][34][35][36]. With respect to fibrinogen adsorption, it has been shown that this protein predominates on most…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…accessibility of the Fc parts of the molecules on the surface to the corresponding neutrophil receptors FcgRs), or simply the ligand density on the surface, which is determined by the physicochemical property of the supporting surface. Our results on the effect of surface-adsorbed albumin are in agreement with earlier observations [13][14][15][34][35][36]. With respect to fibrinogen adsorption, it has been shown that this protein predominates on most…”
Section: Discussionsupporting
confidence: 93%
“…Liu et al surfaces [37]. Owing to the fact that fibrinogen has been suggested to be of great importance in the acute inflammatory response, reflected by the accumulation of neutrophils on implanted fibrinogen-coated surfaces [21,34,35], we expected some cellular activation during neutrophil interaction with such a surface. However, fibrinogen coating on our glass surfaces failed to activate the neutrophils to any detectable degree.…”
mentioning
confidence: 98%
“…Molecular dynamic simulation studies by Dragneva et al suggested that the "end-on" orientation of fibrinogen, in particular, strongly affects the secondary structure content of the D-domain, with consequent exposure of the previously occult recognition sites (e.g., residues 190-202 of the fibrinogen γ-chain) involved in the immune response. [49,50] Recent observations [11,51] that protein adsorption configuration can be guided by surface topographical features allow us to postulate that a reasonable starting point for a healthcare material-implant design would be to eliminate/tune surface topographical features in a way to inhibit protein "end-on" orientation.…”
Section: Protein Adsorption Guided By Surface Physicochemical Factorsmentioning
confidence: 99%
“…The question of why materials with diverse surface properties elicit the same FBR has troubled investigators for more than two decades (3)(4)(5). It is believed that implants acquire a protein coat immediately after implantation, which serves as a stimulus for the development of the FBR (6)(7)(8)(9)(10), and it has been suggested that fibrinogen is a critical component of this protein coat (10,11). Adsorption of proteins can be influenced by the surface properties of the material and may lead to modification of the FBR (3,(12)(13)(14)(15).…”
mentioning
confidence: 99%